2017
DOI: 10.1051/epjconf/201716002007
|View full text |Cite
|
Sign up to set email alerts
|

Non-adiabatic pulsations in ESTER models

Abstract: Abstract. One of the greatest challenges in interpreting the pulsations of rapidly rotating stars is mode identification, i.e. correctly matching theoretical modes to observed pulsation frequencies. Indeed, the latest observations as well as current theoretical results show the complexity of pulsation spectra in such stars, and the lack of easily recognisable patterns. In the present contribution, the latest results on non-adiabatic effects in such pulsations are described, and we show how these come into play… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…In this context, it may be remarked that the amplitude of the observed line profile changes peaks towards the line center whereas models often predict larger amplitudes in the wings (e.g. Reese et al 2017) or at least a flatter amplitude distribution across the profile than observed in π Aqr. Certainly, specific asteroseismic modelling of π Aqr is now required, but this goes beyond the scope of this paper.…”
Section: π Aqrmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, it may be remarked that the amplitude of the observed line profile changes peaks towards the line center whereas models often predict larger amplitudes in the wings (e.g. Reese et al 2017) or at least a flatter amplitude distribution across the profile than observed in π Aqr. Certainly, specific asteroseismic modelling of π Aqr is now required, but this goes beyond the scope of this paper.…”
Section: π Aqrmentioning
confidence: 99%
“…For π Aqr, using the stellar parameters of Bjorkman et al (2002), the rotational period amounts to 1.2 d. Since the pulsation frequency detected in spectroscopic and photometric data is ∼12 d −1 , the ratio between pulsation and rotation frequencies is about 14, which is quite high. General asteroseismic modelling applicable to fast rotators begins to be performed, with the first steps towards similar diagnostics as in Telting & Schrijvers (1997) being recently made (Reese et al 2017, -see also pioneering models accounting for first-order effects of rotation in Townsend 1997; Maintz et al 2003). In this context, it may be remarked that the amplitude of the observed line profile changes peaks towards the line center whereas models often predict larger amplitudes in the wings (e.g.…”
Section: π Aqrmentioning
confidence: 99%
“…HD220811, which is quite similar to Altair as far as T eff and Vsini are concerned, also shows a similar number of frequencies. This point is reminiscent of the theoretical (preliminary) result of Reese et al (2017), which shows that as the rotation rate increases, mode excitation is less and less efficient. In other words, rotation tends to stabilise modes otherwise destabilised by the κ-mechanism.…”
Section: Discussionmentioning
confidence: 64%
“…The probable similarity of Altair and HD220811 as far as their oscillation spectrum and spectral type are concerned, together with their very fast rotation (V eq ∼ 300 km s −1 ), may illustrate the result of Reese et al (2017) that fast rotation Notes. The six starred frequencies are new and complete those detected by Buzasi et al (2005).…”
Section: Hd220811: Potential Sister Of Altairmentioning
confidence: 93%
“…The probable similarity of Altair and HD220811 as far as their oscillation spectrum and spectral type are concerned, together with their very fast rotation (V eq ∼ 300 km/s), may illustrate the result of Reese et al (2017) that fast rotation reduces the number of excited modes in a star. The parallel study of these two stars, and others with the same features, will be very useful to better appreciate all the effects of rotation.…”
Section: Hd220811: Potential Sister Of Altairmentioning
confidence: 96%

Seismology of Altair with MOST

Dizès,
Rieutord,
Charpinet
et al. 2021
Preprint
Self Cite